Comparison of Cecal Microbiota and Performance Indices Between Lean-Type and Fatty-Type Pekin Ducks - Yang, Tingshuo; Jiang, Yong; Tang, Jing; Chang, Guobin; Zhao, Wenming; Hou, Shuisheng; Chen, Guohong (Frontiers in Microbiology, 2022)
Fatty-type (FT) Pekin ducks exhibit higher lipid deposition than lean-type (LT) ducks. The gut microbiota plays an important role in modulating fat metabolism. We compared the growth performance, slaughter performance, and cecal microbiota of FT and LT Pekin ducks and analyzed the role of cecal microbiota in lipid deposition in Pekin ducks. A total of 140 1-day-old FT and LT Pekin ducks with similar body weights were randomly assigned to 10 cages, with 14 ducks in each replicate. All ducks were fed commercial diets from 28 to 42 days of age. Results showed that the average body weight and feed intake of FT ducks were higher than those of LT ducks. The breast muscle and eviscerated percentages of LT ducks were higher than those of FT ducks; the abdominal fat and sebum percentages of LT ducks were lower than those of FT ducks at 6 weeks of age (P < 0.01). 16S DNA sequencing of the cecal microbiota revealed that the bacterial abundance differed between FT and LT ducks at 4 and 6 weeks of age. The abundance of Firmicutes was higher, while that of Fusobacteria and Fusobacterium was lower in LT ducks than in FT ducks at 4 weeks of age. The abundance of Spirochaetes was higher, while that of Firmicutes and Bacteroides was lower in LT ducks than in FT ducks at 6 weeks of age. The abundance of Spirochaetes and Brachyspira in LT ducks was higher at 6 weeks than at 4 weeks of age. Interestingly, the abundance of Firmicutes and Bacteroides in FT ducks was higher at 6 weeks of age than at 4 weeks of age, while that of Fusobacteria and Fusobacterium was lower at 6 weeks than at 4 weeks of age. Linear discriminant analysis effect size analysis showed that Spirochaetes, Brachyspira, Alistipes, Campylobacter, Megamonas, Butyricicoccus, and Fusobacteria may be involved in the fat metabolism pathway as specific markers. We reveal the differences in microbial abundance in the cecal microbiota between FT and LT Pekin ducks and provide an insight into the role of cecal microbiota in lipid deposition in Pekin ducks.